Translation and pilot testing of a measure to assess hypertension self-care activities among Hispanics. Issue 4 (19th May 2018) - Warren-Findlow, Jan; Coffman, Maren J.; Karp, Celia A.
ABSTRACT: Objective: Hispanics in the US have high rates of uncontrolled hypertension in comparison to non-Hispanic whites. This pilot study reports on the translation of a validated measure, the Hypertension Self-Care Activity Level Effects (H-SCALE), for use with Spanish speakers. The H-SCALE assesses Hispanics' adherence to lifestyle activities that contribute to primary and secondary risk reduction of high blood pressure. Design: Cross-sectional data were collected from Hispanic primary care patients attending a free health clinic in Charlotte, NC. We performed basic psychometric tests and calculated descriptive statistics to assess adherence rates to recommended hypertension self-care behaviors. Results: Participants were primarily female, under age 50 and had a high-school education or less; 48% were from Mexico. Internal consistency of all H-SCALE subscales was acceptable to good. Most participants were non-smokers (80%) and alcohol abstainers (85%). Participants had low adherence to weight management practices, physical activity and healthy eating habits. One-third of those with hypertension were adherent to medication regimens. Conclusion : The Spanish version of the H-SCALE is a reliable and useful tool for clinicians working with Hispanic adults. Based on these findings, all adult Hispanics need lifestyle behavior counseling for primary and secondary prevention of hypertension and other chronic diseases. The H-SCALE can provide valuable information to clinical and public health practitioners focused on chronic disease prevention and management.